Volume 3: Heat Transfer, Parts a and B 2006
DOI: 10.1115/gt2006-90251
|View full text |Cite
|
Sign up to set email alerts
|

LES and RANS Investigations Into Buoyancy-Affected Convection in a Rotating Cavity With a Central Axial Throughflow

Abstract: The buoyancy-affected flow in rotating disk cavities, such as occurs in compressor disk stacks, is known to be complex and difficult to predict. In the present work, large eddy simulation (LES) and unsteady Reynolds-averaged Navier-Stokes (RANS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Bohn et al [28] simulated their rig [20] with a laminar, compressible, time-dependent flow solver, confirming the experimentally observed flow structures rotating slower than the discs. Sun et al [29] reported LES and URANS calculations of Long et al's [21] experiment, with LES showing better agreement with the measurements (within 25%) than URANS, in terms of the shroud Nu. Tian et al [30] reported adequate prediction results of Farthing et al's [19] experiment, through steady state simulations.…”
Section: Open Rotating Cavity With Axial Throughflowmentioning
confidence: 99%
“…Bohn et al [28] simulated their rig [20] with a laminar, compressible, time-dependent flow solver, confirming the experimentally observed flow structures rotating slower than the discs. Sun et al [29] reported LES and URANS calculations of Long et al's [21] experiment, with LES showing better agreement with the measurements (within 25%) than URANS, in terms of the shroud Nu. Tian et al [30] reported adequate prediction results of Farthing et al's [19] experiment, through steady state simulations.…”
Section: Open Rotating Cavity With Axial Throughflowmentioning
confidence: 99%
“…23 and Sun et al. 24 The Hydra 3D model solution was similar to the axisymmetric case except on “Line-2” and for x/x o > 1.04, in Figure 15. This was due to the presence of the holes in the 3D model.…”
Section: Cfd Modelsmentioning
confidence: 63%
“…The flow field may exhibit large counter-rotating vortices (cyclonic and anti-cyclonic regions) with their axis parallel to the axis of rotation. Evidence of these macro-structures can be found in the experiments of Farthing et al [2], Bohn et al [3], Günther et al [4] or in the numerical simulations of Tian et al [5], Sun et al [6], Puttock-Brown et al [7] and Owen et al [8].…”
Section: Introductionmentioning
confidence: 93%